2012
DOI: 10.3390/s120405170
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Unique Properties of Zeolites in the Development of Gas Sensors

Abstract: The unique properties of microporous zeolites, including ion-exchange properties, adsorption, molecular sieving, catalysis, conductivity have been exploited in improving the performance of gas sensors. Zeolites have been employed as physical and chemical filters to improve the sensitivity and selectivity of gas sensors. In addition, direct interaction of gas molecules with the extraframework cations in the nanoconfined space of zeolites has been explored as a basis for developing new impedance-type gas/vapor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 67 publications
0
59
0
4
Order By: Relevance
“…Estos sensores, que se basan en las propiedades electroquímicas o modulación de la resistencia eléctrica del material expuesto a diferentes gases, han venido tomando importancia en el monitoreo de la polución del aire [12], [13].…”
Section: Introductionunclassified
“…Estos sensores, que se basan en las propiedades electroquímicas o modulación de la resistencia eléctrica del material expuesto a diferentes gases, han venido tomando importancia en el monitoreo de la polución del aire [12], [13].…”
Section: Introductionunclassified
“…2) and ion exchange properties. The processes that include formation of complex-cations on zeolites are important to develop industrially significant materials, such as catalysts [10][11][12] and photocatalysts [13], medicine [14], sensor materials [31,32], feeding additives for farm animals [33], etc.…”
Section: Future Applications Of Zeolitesmentioning
confidence: 99%
“…3,4 The latter properties confer to silver-zeolite composites the ability to optically respond to external stimuli, such as variations of moisture within the zeolite scaffold [6][7][8] or the presence of determined gases; therefore their use as water vapor and gas sensors has been suggested. 9,10 In a recent study we have demonstrated that the optical response of Ag-zeolites to moisture is not only correlated to changes in the absorption or quenching of their emission but also to the appearance of different emission colors with respect to their water content. 5 The stabilization of silver clusters in partially Li exchanged LTA zeolites led to the formation of a moisture-responsive material in which changes in the relative low humidity scale were reflected in a dynamic color change from a blue to green/yellow emission in dehydrated and hydrated samples, respectively.…”
Section: Introductionmentioning
confidence: 99%